2022
DOI: 10.1002/bmc.5330
|View full text |Cite
|
Sign up to set email alerts
|

Stability‐indicating liquid chromatography method development and validation for impurity profiling of montelukast sodium in bulk drug and tablet dosage form

Abstract: Montelukast sodium (MLS) is a leukotriene receptor antagonist drug used in the treatment of asthma, bronchospasm, allergic rhinitis and urticaria. A reversed-phase high performance liquid chromatography method was developed to separate, identify and quantitative determination of MLS and its eight known organic impurities in tablet dosage form using a C 18 column and mobile phases consisting of a gradient mixture of pH 2.5 phosphate buffer and acetonitrile. The stability-indicating character of the developed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The methodology that was designed and established as part of the intended investigation was evaluated in accordance with International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) requirements, and the results showed that it was specific, linear, accurate, precise, and robust (ICH, 2005; Narasimha & Chandrasekar, 2019; United States Pharmacopeia, 2021). The results of the forced degradation study proved that the developed HPLC method possesses the stability‐indicating characteristics, in addition to being specific and selective in the separation and quantitative determination of BXM and its organic related impurities in drug substance and drug product (Bakshi & Singh, 2002; Blessy et al, 2014; Boppy et al, 2022; Carr & Wahlich, 1990; Ettaboina, Katakam, & Dongala, 2022; Ettaboina, Nakkala, & Chathalingath, 2022; Katakam, Ettaboina, & Dongala, 2021; Katakam, Ettaboina, & Marisetti, 2021; Lakka & Goswami, 2012; Lakka et al, 2021; Lakka et al, 2022; Lakkireddy et al, 2015; Mohan et al, 2022; Narasimha et al, 2011; Narasimha et al, 2019; Narasimha et al, 2020; Narasimha et al, 2022; Siva et al, 2022; Snyder et al, 2010). In addition, the experimental studies utilizing the LC–MS technique were carried out to evaluate the mass spectral data of newly formed unknown impurities when the sample was subjected to oxidative stress testing.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology that was designed and established as part of the intended investigation was evaluated in accordance with International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) requirements, and the results showed that it was specific, linear, accurate, precise, and robust (ICH, 2005; Narasimha & Chandrasekar, 2019; United States Pharmacopeia, 2021). The results of the forced degradation study proved that the developed HPLC method possesses the stability‐indicating characteristics, in addition to being specific and selective in the separation and quantitative determination of BXM and its organic related impurities in drug substance and drug product (Bakshi & Singh, 2002; Blessy et al, 2014; Boppy et al, 2022; Carr & Wahlich, 1990; Ettaboina, Katakam, & Dongala, 2022; Ettaboina, Nakkala, & Chathalingath, 2022; Katakam, Ettaboina, & Dongala, 2021; Katakam, Ettaboina, & Marisetti, 2021; Lakka & Goswami, 2012; Lakka et al, 2021; Lakka et al, 2022; Lakkireddy et al, 2015; Mohan et al, 2022; Narasimha et al, 2011; Narasimha et al, 2019; Narasimha et al, 2020; Narasimha et al, 2022; Siva et al, 2022; Snyder et al, 2010). In addition, the experimental studies utilizing the LC–MS technique were carried out to evaluate the mass spectral data of newly formed unknown impurities when the sample was subjected to oxidative stress testing.…”
Section: Introductionmentioning
confidence: 99%
“…for the separation and quantitative estimation of S ‐enantiomer of LA from both the drug substance and drug product (tablet dosage form). The stability‐indicating properties of the developed test method were assessed using forced degradation studies (Bakshi & Singh, 2002; Blessy et al, 2014; Boppy et al, 2022; Carr & Wahlich, 1990; Ettaboina, Katakam, & Dongala, 2022; Ettaboina, Nakkala, & Chathalingath, 2022; ICH, 1996; ICH, 2003; Katakam, Ettaboina, & Dongala, 2021; Katakam, Ettaboina, & Marisetti, 2021; Lakka & Goswami, 2012; Lakka et al, 2021, 2022; Lakkireddy et al, 2015; Mohan et al, 2022; Nagulancha et al, 2023; Narasimha et al, 2011, 2019, 2020, 2022; Siva et al, 2022; Snyder et al, 2010). The developed test method was validated in accordance with ICH (International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use) guidelines for specificity, linearity, accuracy, precision, and robustness (ICH, 2005; Narasimha & Chandrasekar, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…for the separation and quantitative estimation of S-enantiomer of LA from both the drug substance and drug product (tablet dosage form). The stability-indicating properties of the developed test method were assessed using forced degradation studies (Bakshi & Singh, 2002;Blessy et al, 2014;Boppy et al, 2022;Carr & Wahlich, 1990;Ettaboina, Katakam, & Dongala, 2022;Ettaboina, Nakkala, & Chathalingath, 2022;ICH, 2003;Katakam, Ettaboina, & Dongala, 2021;Katakam, Ettaboina, & Marisetti, 2021;Lakka & Goswami, 2012;Lakka et al, 2021Lakka et al, , 2022Lakkireddy et al, 2015;Mohan et al, 2022;Nagulancha et al, 2023;Narasimha et al, 2011Narasimha et al, , 2020Narasimha et al, , 2022Siva et al, 2022;Snyder et al, 2010)…”
mentioning
confidence: 99%
“…Stability‐indicating liquid chromatography is a validated analytical test procedure that accurately and precisely measures the drug in drug substance or drug product free from impurities (process or degradation products), excipients used in drug formulation and solvent peaks used for the analysis. At present, high‐performance liquid chromatography (HPLC), ultra‐performance liquid chromatography (UPLC) and liquid chromatography coupled with mass spectrometry (LC–MS) are most frequently used to develop SIM and estimate the amount of impurities (Blessy et al, 2014; Lakka et al, 2021; Lakkireddy et al, 2015; Narasimha et al, 2019, 2020, 2022; Narasimha & Chandrasekar, 2019; Pasham et al, 2022). SIM plays an important role in analytical method development for the separation and quantitative estimation of organic impurities (process related impurities) and degradation products (DPs) which are most likely to be generated during the stress testing and storage of drugs owing to the environmental factors of heat, light and humidity.…”
Section: Introductionmentioning
confidence: 99%
“…At present, high-performance liquid chromatography (HPLC), ultraperformance liquid chromatography (UPLC) and liquid chromatography coupled with mass spectrometry (LC-MS) are most frequently used to develop SIM and estimate the amount of impurities (Blessy et al, 2014;Lakka et al, 2021;Lakkireddy et al, 2015;Narasimha et al, , 2020Narasimha et al, , 2022Pasham et al, 2022). SIM plays an important role in analytical method development for the separation and quantitative estimation of organic impurities (process related impurities) and degradation products (DPs) which are most likely to be generated during the stress testing and storage of drugs owing to the environmental factors of heat, light and humidity.…”
mentioning
confidence: 99%